Analisis Makna Idiomatik Dalam Artikel Berita Radar Solo Harian Jawa Pos Sebagai Implementasi Pembelajaran Bahasa Indonesia Di Kelas XI SMK Muhammadiyah Delanggu - Astuti, Elly; , Drs.Yakub Nasucha,M.Hum (2016)
The porpose research to similarity form describe idiomatic and expression along with idiomatic meaning which there are in new article Radar Solo daily Jawa Pos edition November 2015 as study implementation in class XI SMK Muhammadiyah Delanggu. Research object become attention in this research is idiomatic meaning and expression detail as study implementation of Indonesion language. Method of data collection in this research is book technique, correct reading, and note, while analysis method of data use correspond and method distribute. Result of this indicate research that is (1) idiom referred [as] also with expression, because both owning same meaning content. (2) idiomatic form there are in new article Radar Solo daily Jawa Pos edition November 2015 have kinds two of full idiom amount tenty four data and some of idiom amounting to eighteen data. Besides, expression detail in the form of two word expression amount to twelve data, three word or more expression amounting to three data, old expression do not be found by its data, new expression amount to twenty two data, foreign Ianguage expression amount to four data, vernacular expression amount to three data. Its applying result of student finding data of sort to be analysed in tables. Keyword: idiomatic, news article, study, meaning, sentence